Respon Produksi Biomassa Stevia rebaudiana Dengan Pemberian Berbagai Pupuk Organik: (Tinjauan Literatur) - Ananda, Aldan; Tantawi, Ahmad Rafiqi (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Stevia rebaudiana (Bertoni) is a natural sweetener plant that is increasingly in demand because of the content of steviol glycosides in its leaves which is safe for people with diabetes and obesity. The biomass production of stevia leaves is an important indicator in determining the quality and quantity of glycosides produced. This study aims to analyze the influence of various types of organic fertilizers on the growth and production of Stevia rebaudiana biomass through a literature study. This study uses a descriptive-qualitative method by examining 30 relevant scientific sources from national and international journals in the period 2008–2023. The results of the study show that organic fertilizers such as manure, compost, cascing, and plantagar are able to significantly increase vegetative growth, root system, and leaf glycoside content. The effectiveness of fertilizers is greatly influenced by environmental factors such as soil pH, temperature, and light intensity. The use of paranet and liming is an adaptive strategy to create microclimate conditions that support nutrient absorption. In conclusion, the combination of organic fertilization and proper environmental management can optimize the production of stevia biomass in a sustainable and environmentally friendly manner.